2004
DOI: 10.1074/jbc.m307702200
|View full text |Cite
|
Sign up to set email alerts
|

EHD2 and the Novel EH Domain Binding Protein EHBP1 Couple Endocytosis to the Actin Cytoskeleton

Abstract: Here we identified two novel proteins denoted EH domain protein 2 (EHD2) and EHD2-binding protein 1 (EHBP1) that link clathrin-mediated endocytosis to the actin cytoskeleton. EHD2 contains an N-terminal P-loop and a C-terminal EH domain that interacts with NPF repeats in EHBP1. Disruption of EHD2 or EHBP1 function by small interfering RNA-mediated gene silencing inhibits endocytosis of transferrin into EEA1-positive endosomes as well as GLUT4 endocytosis into cultured adipocytes. EHD2 localizes with cortical a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
181
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(194 citation statements)
references
References 53 publications
12
181
1
Order By: Relevance
“…Transfection of wild type EHD2 did not disturb myoblast fusion. Consistent with normal myoblast fusion, wild type EHD2 and myoferlin were colocalized at sites on the membrane and throughout the cytosol in a pattern consistent with previous reports describing a role for EHD2 in coupling endocytosis to actin cytoskeletal dynamics (28).…”
Section: Delayed Endocytic Recycling In Myoferlin Nullsupporting
confidence: 89%
See 1 more Smart Citation
“…Transfection of wild type EHD2 did not disturb myoblast fusion. Consistent with normal myoblast fusion, wild type EHD2 and myoferlin were colocalized at sites on the membrane and throughout the cytosol in a pattern consistent with previous reports describing a role for EHD2 in coupling endocytosis to actin cytoskeletal dynamics (28).…”
Section: Delayed Endocytic Recycling In Myoferlin Nullsupporting
confidence: 89%
“…It has previously been observed that EHD2 and its binding partner EHD2-binding protein 1 (EHBP1), localize to adjacent structures in regions of endocytosis and actin dynamics such as ruffled membranes and only colocalize in regions where the adjacent structures overlap (28). It is possible that myoferlin and EHBP1 compete for binding on EHD2 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…1 A). Two immunoreactive species were observed of apparent sizes of 68 kDa (major) and 65 kDa (minor), corresponding to the sizes of Pincher (Shao et al, 2002) and the highly homologous Pincher family members, rEHD1/2 (Mintz et al, 1999;Guilherme et al, 2004), respectively. The 68 kDa protein was positively identified as Pincher in SCG neurons overexpressing an HA-tagged Pincher cDNA ( Fig.…”
Section: Pincher Mediates Trka Internalization and Endosomal Erk5 Sigmentioning
confidence: 99%
“…Vertebrate EHDs show a distinct tissue expression pattern [7,8,[11][12][13] and intracellular localization. EHD1 was localized mainly to the endocytic recycling compartment (ERC) [7] with some localization on the plasma membrane and early endosomes [14,15], while EHD2 was localized to the plasma membrane [16,17]. EHD3 was located on early endosomes and the perinuclear tubular and vesicular structures of the recycling compartment [12,18] and EHD4 was localized to the plasma membrane, to vesicular structures [19] and to early endosomes [20].…”
Section: Introductionmentioning
confidence: 99%